2016
DOI: 10.18632/oncotarget.11837
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells promote melanoma colonization of lungs

Abstract: Mast cells have been implicated in malignant processes, mainly through clinical correlative studies and by experiments performed using animals lacking mast cells due to defective c-kit signaling. However, mast cell-deficient mouse models based on c-kit defects have recently been questioned for their relevance. Here we addressed the effect of mast cells in a tumor setting by using transgenic Mcpt5-Cre+ R-DTA+ mice, in which the deficiency of mast cells is independent of c-kit defects. Melanoma cells (B16.F10) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 47 publications
3
32
0
Order By: Relevance
“…qPCR was performed as described previously. 35 The RNA isolation kit was from Macherey-Nagel (Düren, Germany), and the cDNA synthesis kit was from Bio-rad (Solna, Sweden). SYBR GreenER SuperMix from Invitrogen (Carlsbad, CA, USA) was used.…”
Section: Methodsmentioning
confidence: 99%
“…qPCR was performed as described previously. 35 The RNA isolation kit was from Macherey-Nagel (Düren, Germany), and the cDNA synthesis kit was from Bio-rad (Solna, Sweden). SYBR GreenER SuperMix from Invitrogen (Carlsbad, CA, USA) was used.…”
Section: Methodsmentioning
confidence: 99%
“…To gain more mechanistic insight into the role of MCs in melanoma, we previously examined melanoma progression in wild‐type (WT) mice versus mice that lacked connective tissue‐type MCs altogether (Dudeck et al, ), using a model of melanoma colonization to the lung. In that study, we found that MCs had an overall detrimental impact (Öhrvik et al, ) and to dissect the underlying mechanism we assessed mice lacking all of the MC proteases in the same model. Strikingly, we found that mice with global MC protease deficiency, contrary to the mice lacking MCs altogether, developed larger tumors than did WT mice (Grujic et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that mast cells accumulate in a variety of malignant tumors, such as melanoma, Hodgkin's lymphoma and chronic lymphocytic leukemia, pancreatic, prostate and esophageal cancer (5). Some reports have shown that the high number of MCs is associated with a good prognosis (6), while others have noticed their association with poor prognosis and distant metastasis (7)(8)(9). Some reports suggest that mast cells play a promoting role in the occurrence and development of malignant tumors (10,11).…”
mentioning
confidence: 99%